2021
DOI: 10.3390/ijerph18083935
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette and E-Cigarettes Dual Users, Exclusive Users and COVID-19: Findings from Four UK Birth Cohort Studies

Abstract: Introduction: The relationship between current cigarette and electronic cigarette (e-cigarette) dual use, exclusive use and COVID-19-related measures are still unclear. This study aims to assess the association between different tobacco use patterns and coronavirus disease 2019 (COVID-19) symptoms, testing, self-reported infection and social distancing behaviors in the United Kingdom (UK). Methods:Data come from the first wave of the Centre for Longitudinal Studies (CLS) COVID-19 survey, comprising four birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…A study in Italy has also shown that during the COVID-19 pandemic, most exclusive cigarette smokers had considered quitting, but most exclusive e-cigarette users had not 15 . A UK study found that current dual-use of cigarettes and e-cigarette was associated with 2.15-fold higher odds for reporting COVID-19 infection 38 . Many HTP and e-cigarette dual users of cigarettes were more nicotine dependent than exclusive cigarette users 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in Italy has also shown that during the COVID-19 pandemic, most exclusive cigarette smokers had considered quitting, but most exclusive e-cigarette users had not 15 . A UK study found that current dual-use of cigarettes and e-cigarette was associated with 2.15-fold higher odds for reporting COVID-19 infection 38 . Many HTP and e-cigarette dual users of cigarettes were more nicotine dependent than exclusive cigarette users 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Dual users also had the highest percentage of COVID-19 related symptoms (eg, dry cough, fever, loss of sense of smell or taste or shortness of breath) in the past 2 weeks. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Although e-cigarette use is often touted as a safer alternative to tobacco combustion, the potential long-term health effects of e-cigarette use are not well understood [ 1 , 2 , 3 , 4 ]. The rapid increase of e-cigarette use, especially among adolescents, could present itself as an emerging public health concern [ 3 , 5 , 6 , 7 , 8 , 9 ], including potential associations with COVID-19 symptoms [ 10 , 11 , 12 ]. Although e-cigarettes are perceived to be safer than traditional combustion cigarettes, a specific health problem associated with e-cigarettes is the long-term exposure of users to potentially toxic metals.…”
Section: Introductionmentioning
confidence: 99%